Effectiveness Of Administering Olive Oil Against Diaper Rash In Babies Aged 0-36 Months At Pmb Cahyati Bogor, West Java, 2023 - Nur Hikmi Meilita Sari; Omega DR Tahun (International Journal of Health and Pharmaceutical (IJHP), 2024)
Background: In The World, It Is Estimated That Skin Irritation (Diaper Rash) Occurs In Babies In 25% Of The 6,840,507,000 Babies Born. The Prevalence Of Babies Affected By Diaper Rash In West Java In 2020 Was 52.7%. Diaper Rash Can Cause Red Spots, Itching, Skin Irritation, And Discomfort In Sensitive Areas Of Toddlers. Usually Caused By Humidity, Fungus And Bacteria That Develop In These Sensitive Areas. The Aim Of This Research Is To Find Out How Effective The Use Of Olive Oil Is In Treating Diaper Rash. Research Method: The Research Used Was Pre-Experimental Using A One Group Pretest-Posttest Design, And With A Prospective Approach. This Research Was Conducted At Pmb Cahyati Bogor, West Java. The Research Sample Was 30 Respondents Taken Using Total Sampling Technique. Research Results: Based On The Results Of Non-Parametric Statistical Tests, The Significance Value Was 0.000 < 0.005, It Can Be Concluded That There Is An Effect Of Giving Olive Oil On Diaper Rash In Toddlers At Pmb Cahyati, Bogor, West Java In 2023. Suggestion: It Is Hoped That Respondents Can Use Extra Virgin Olive Oil As A Medicine To Treat Diaper Rash In Toddlers Who Experience Diaper Rash And Can Be Used For Other Health Needs.